Long-term uterine balloon tamponade for treatment and obliteration of ruptured uterine pseudoaneurysm - Jun Takeda; Shintaro Makino; Chihiro Hirai; Yota Shimanuki; Tetsunori Inagaki; Atsuo Itakura; Satoru Takeda (Elsevier, 2018)
Objective: Rupture of uterine artery pseudoaneurysm (UAP) is a life-threatening event after childbirth. Hysterectomy or uterine arterial embolization was often needed for hemostasis. However, such procedures may cause severe morbidities for these women. To estimate the efficacy of uterine balloon tamponade (UBT) for controlling ruptured UAP bleeding, a retrospective analysis in a single teaching hospital was performed. Materials and methods: We reviewed the medical record of Juntendo University Hospital in 2015. All the women diagnosed with UAP were recruited to this study and management for UAP was investigated. Results: Three women were treated with UBT for ruptured UAP. All cases achieved hemostasis. One case had recurrent UAP after 24 h of UBT, and was retreated with UBT for a longer duration. The UAP was obliterated after more than 2 days of UBT in all cases. Conclusion: UBT has potential as a therapeutic technique not only for treatment of a ruptured UAP but also for obliteration of a UAP.